The Illocution Functions in Twilight Movie Dialogues: From Politeness Study Point of View - Devi Mulatsih (Jurnal Lingua Idea, 2021)
This research aims to analyze politeness based on the types of illocution functions that belong to Leech’s theory. This study is descriptive qualitative research and the data were collected through the literature review study. Data source taken from Twilight movie dialogues, to analyze the illocutions function used in daily life. The results of the analysis displayed in percentage form based on Bungin formula. This research used 208 data from the utterances of movie dialogues that represented the types. The analysis focused on two illocution functions, such as competitive and convivial for the 208 utterances which represent all the data. The result showed that Competitive (50,96%) and Convivial (49,04%) are the most dominant utterances which appear between the characters in Twilight movie dialogues.